Modern Scattering-Type Scanning Near-Field Optical Microscopy for Advanced Material Research - Chen, Xinzhong (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.